Improving PKN Learning Outcomes Through The Role Playing Learning Method in Class V of SD Negeri Lawe Sempilang Kec Lawe Alas District. Southeast Aceh 2023/2024 Academic Year - Anggrayni Tanjung, Ricka (Journal of Elementary School Education, 2024)
The Civics learning process at SD Negeri Lawe Sempilang rarely uses learning methods that attract the attention and activeness of all students in the class. Only a few students are active and most of the other students do not understand the Civics material taught by the teacher. So that the level of understanding and absorption of explanations from the teacher when the learning process between students is not the same. This research is a classroom action (PTK) with the research subject being the fifth grade students of SD Negeri Lawe Sempilang in the 2023/2024 academic year. The data test method used in this research is the test method, interview and observation. The collected data were analyzed using descriptive analysis. The use of the role playing method can improve student achievement in grade V SD Negeri Lawe Sempilang on the subject of respecting collective decisions. In the research that has been done it is proven that the activeness of students in participating in the learning process is increasing. This can be seen from the results of the tests that have increased in the final test of cycle 1 the average score of students is 74.45 and in cycle 2 the average value is 82.5. Likewise, in terms of completeness, it also increases from cycle 1 to cycle 2, namely 63.6%, increasing to 90.9%.